STRATEGI BAURAN PEMASARAN DAN KEPERCAYAAN TERHADAP KEPUASAN PASIEN PUSKESMAS SRONDOL - Lutfy Purnanta Anzie; Edwin Zusrony; Nada Trashtya Ibaneza (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2022)
This study aims to measure the effect partially and simultaneously on the marketing mix variable and the trust variable on patient satisfaction at PUSKESMAS Srondol Semarang city. The object of the research is the Srondol PUSKESMAS patients who have used the service facilities in the last 3 months or from January to March 2021 a total of 30 people. Collecting data using an online questionnaire/questionnaire using Google Form and measured by a Likert scale. The research method uses multiple linear regression with the help of SPSS 23 data processing. The results show that the marketing mix variable and the trust variable have a significant influence on patient satisfaction at PUSKSMAS Srondol and marketing mix variables have a dominant effect on patient satisfaction at PUSKSMAS Srondol in Semarang.